Bantuan Teknis Penyusunan Justifikasi Rehabilitasi Sun Shading pada Gedung KANWIL DJP Bengkulu-Lampung di Bandar Lampung - Lestari, Suci; Putri, Tiya Suryadi; Faris, Muhammad Faisal; Megawati, Puan Jati (Nemui Nyimah, 2024)
The response to a request from the Bengkulu-Lampung Regional Office of the Directorate General of Taxes (Kanwil DJP) regarding technical justification for the condition of sun shading in the tax service building, this is an effort to be directly involved in implementing the Tri Dharma of Higher Education tasks. The existing problems are related to damage and decreased efficiency of the sun shading system installed on the building facade. This damage is caused by material degradation, non-optimal installation, and exposure to extreme environmental conditions. The proposed rehabilitation plan aims to improve and optimize the sun shading function so that it can function optimally again. Rehabilitation measures include replacement of damaged panel materials, reinstallation with stronger fastenings, and increased protection against extreme environmental influences. This rehabilitation is expected to not only increase energy efficiency and comfort for building users, but also improve the visual image of the building as a representative public facility